2017
DOI: 10.1159/000478893
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy: Value for Melanoma Therapy?

Abstract: Treatment of metastatic melanoma has undergone tremendous changes over the past few years. There are now highly effective systemic therapies available: targeted therapy with BRAF and MEK inhibitors in BRAF-V600-mutant melanoma and immunotherapies, including PD-1 antibodies with or without CTLA-4 antibody, that can be used regardless of mutational status. However, long-term tumor control is only achieved in a minority of patients. Liquid biopsy using circulating tumor cells, circulating tumor DNA (ctDNA), circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
(62 reference statements)
0
8
0
Order By: Relevance
“…Liquid biopsy, including CTCs, ctDNA, and circulating tumor RNA (ctRNA) has only been studied in small patient cohorts treated by use of ICI (mainly CTLA4ab) for melanoma. An association between treatment response and a decrease in CTCs and ctDNA has been found for targeted therapy, but not for ICI ( 94 ). Methodological improvements offer new opportunities for CTC detection, as has been very recently described for microfluidic enrichment of melanoma CTCs combined with RNA-based droplet digital PCR quantitation ( 64 ).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…Liquid biopsy, including CTCs, ctDNA, and circulating tumor RNA (ctRNA) has only been studied in small patient cohorts treated by use of ICI (mainly CTLA4ab) for melanoma. An association between treatment response and a decrease in CTCs and ctDNA has been found for targeted therapy, but not for ICI ( 94 ). Methodological improvements offer new opportunities for CTC detection, as has been very recently described for microfluidic enrichment of melanoma CTCs combined with RNA-based droplet digital PCR quantitation ( 64 ).…”
Section: Blood Biomarkersmentioning
confidence: 99%
“…The most frequent and explored alterations are BRAF and NRAS mutations, present in 40–60% and 28% of patients, respectively 24 , 25 . In addition, a high frequency of mutations in the promoter region of TERT gene has been found in melanoma patients with a frequency ranging from 50 to 80% in several studies 24 , 26 , 27 , including Brazilian populations 28 .…”
Section: Introductionmentioning
confidence: 99%
“…Among the many biomarkers used in melanoma, ctDNA is already considered a valuable tool for monitoring the therapy response [44][45][46]. For instance, it has been shown that the increase of ctDNA level in the plasma of patients with BRAF-mutated melanoma treated with targeted therapies precedes the detection of relapses by imaging and by clinical evaluation [47].…”
Section: Circulating Tumor Dnamentioning
confidence: 99%